Measurement of serum interferon alpha in Egyptian patients with systemic lupus erythematosus and evaluation of its effect on disease activity: a case-control study - Fayed, A.; El Menyawi, M.M.; Ghanema, M.; Shaker, O.; Elgohary, R. (Reumatismo, 2020)
Much evidence highlighted the role of interferon alpha (IFN-α) in systemic lupus erythematosus (SLE) and suggested its possible role in assessing disease activity. We measured serum IFN-α in Egyptian SLE patients in order to determine a cutoff value that can be used to distinguish patients from healthy controls and explored its clinical value in monitoring disease activity and different aspects of the disease, in particular lupus nephritis. This cross-sectional, case-control study was conducted on 59 SLE patients and 30 healthy controls. Serum IFN-α was measured in all participants using sensitive enzyme-linked immunosorbent assay (ELISA). SLE patients underwent assessment of disease activity using the SLE disease activity index-2000 (SLEDAI-2K) as well as an evaluation of proteinuria, complement C3 and C4, and serology. Patients with evidence of renal involvement underwent renal biopsy. The median serum IFN-α was 81.8 pg/mL (interquartile range [IQR] 63.4:102.4), which was significantly higher than in healthy controls (median 10.3 pg/mL [IQR 7.3:11.6]) (p